การใช้กากอนินทรีย์เป็นวัตถุดิบในการผลิตแก้วโมเสกเทมเปอร์ - อนุพงศ์ บัวผิน (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This research aimed to prepare a mosaic glass (MG) using three inorganic wastes i.e. silicate residue (SR; 50-70 wt%), iron slag (IS; 10-30 wt%) and soda-lime cullet (SLC; 10-40 wt%) and to develop the strength of mosaic glass by tempering process. The batches were melted at 1400oC with 10oC/min for 1 h. The molten MGs were poured into water to be frit form and then were re-melted at the same condition. The MGs melts were formed by casting in a 5 x 5 x 0.5 cm stainless steel mould. The MGs were annealed at 550oC for 20 min and then were normal cooled. In order to reveal the effects of compositions on the behavior of MGs, the structures were determined with x-ray diffractometer, fourier transform infrared and raman spectrometers. The mechanical, optical, thermal and chemical properties were also investigated such as bulk density (), glossy (GU), abrasiveness, impact strength , microhardness (HV), color, optical transmission (A/d), strain (Tst)-transition (Tg)-softening (Ts) temperatures, coefficient of thermal expansion (CTE), viscosity at 680-720oC, leaching of toxic metals, and acidic/basic resistances. The results showed the selected MGs was prepared using (in wt%) SR 60, IS 30 and SLS 10 representing good melt and flow abilities. It is completely melted representing the only one XRD broad peak. The main structures are [SiO4] units, Si-O-Si asymmetric stretching, Si-Oo and Si-O- stretching vibration bonds. The properties of MGs are bulk density (2.76 g/cm3), glossy (96 GU), abrasiveness (<0.027%), microhardness (749.70 HV), dark brown color, A/d (2.5 cm-1), Tst (590oC), Tg (704oC), Ts (747oC), CTE (7.725x10-6/oC), viscosity at 680 oC (1013.50 Pa.s), resistances for leaching, acidic and basic solutions. The degree of polymerization and covalent bonds increased with the increasing of glass-network formers (SiO2 and Al2O3) from IS. Addition the increase of IS contents are very important on the properties, favouring the increases of microhardness, abrasiveness impact strength, viscosity, Tst-Tg-Ts, acidic and basic resistance, but the decreases of bulk density, glossy, CTE (7.725x10-6/oC). The selected MG was conducted to tempering process with controlling parameters i.e. temperature, retention time and quenching rate. It was found that the selected MG for 5 mm thickness was tempered at 720°C for 250 sec and quenching rate of 46%, resulting to the increase of microhardness up to 1049.61 HV. Moreover, the abrasiveness and impact strength was also increased. These phenomena occurred during tempering process due to the compressive force on two surfaces and tension force at the middle of MG which are moved to equilibrium state.